Market democracy, rising populism, and contemporary ordoliberalism - Malte Dold; Tim Krieger (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2024)
For several decades, what has been called the "liberal cosmopolitan-minded urban elites" set the political agenda of Western democracies (Dold and Krieger 2019a). They aimed at personal freedom and upward social mobility by means of a meritocratic system that was safeguarded by a combination of a competitive market economy, a liberal and open democracy, and the rule of law (Fuest 2018). These elites welcomed the opening of the Iron Curtain as the "end point of mankind's ideological evolution and the universalization of Western liberal democracy" (Fukuyama 1989, 4). However, political realities have challenged this perspective severely in recent years (Dold and Krieger 2019a). Around the globe, but especially in the liberal Western market democracies - i.e., societies in which "markets and democracy have coexisted quite healthily" in the post-World War II era (Chua 2000, 289) - populist movements have gained prominence in public discourse and in some cases even won elections (e.g., in Hungary, the Netherlands, Italy, Poland, or Sweden). There is ongoing debate over the causes of the rise of populist movements in the early 21st century (Gidron and Hall 2017; Guiso et al. 2017; Inglehart and Norris 2017; Mudde and Kaltwasser 2017). While important, our chapter will touch upon this debate only in passing, though, and instead focus on the consequences of populism's rise; in particular, we will ask how to deal with the populist challenge to the liberal order. We do so in three steps, thereby referring to one specific liberal conception, ordoliberalism. Considering ordoliberalism is instructive because, on the one hand, it strives for a "functioning and humane order of the economy, society, law, and the state" (Eucken 1990 [1952], 373; our italics), which is a much broader idea of liberalism than pure economic liberalism. On the other hand, critics argue that ordoliberalism has failed on following up on its own agenda (Dold and Krieger 2019b and 2023). They believe that ordoliberalism is the culprit of various misguided developments since the Eurozone crisis of 2009, which then provided a breeding ground for populism (Algan et al. 2017; Dold and Krieger 2019a). In their view, this is also related to ordoliberalism's - alleged - preference of the rule of law and economic freedom over democratic decision-making.
Keywords: 330